Types of Salmonella paratyphi B and their phylogenetic significance - Barker, Ruth M; Kearney, Gabrielle M; Nicholson, P; Blair, Andrea L; Porter, R. C; Crichton, Pamela B (Journal of medical microbiology, 1988)
Department of Medical Microbiology, University of Dundee Medical School, Ninewells Hospital, Dundee DD1 9SY Received December 7, 1987 Accepted December 11, 1987 Summary . The substrates inositol, rhamnose, d -tartrate and m -tartrate used in fermentation tests with 338 cultures of Salmonella paratyphi B differentiated strains in some phage types to give information that could be used in epidemiological investigations. Xylose in Bitter's medium, the fifth substrate by which 13 of a potential 32 biotypes were identified, differentiated few cultures with the negative character. The possession of a specific type of outer-membrane protein receptor for colicin M or bacteriophage ES18 and the particular type of ribosomal ribonucleic acid present, defined three groups among the phage-typed and biotyped cultures. The possibility that the serotype S. paratyphi B contains clones of different phylogenetic origin and the consequent implications for nomenclature are discussed.